Breed differences in social cognition, inhibitory control, and spatial problem‑solving ability in the domestic dog (Canis familiaris) - Junttila Saara; Valros Anna; Mäki Katariina; Väätäjä Heli; Reunanen Elisa; Tiira Katriina (United Kingdom, 2023)
The extraordinary genetic and behavioural diversity of dog breeds provides a unique opportunity for investigating the heritability of cognitive traits, such as problem‑solving ability, social cognition, inhibitory control, and memory. Previous studies have mainly investigated cognitive differences between breed groups, and information on individual dog breeds is scarce. As a result, findings are often contradictory and inconsistent. The aim of this study was to provide more clarity on between‑ breed differences of cognitive traits in dogs. We examined the performance of 13 dog breeds (N = 1002 dogs) in a standardized test battery. Significant breed differences were found for understanding of human communicative gestures, following a human’s misleading gesture, spatial problem‑solving ability in a V‑detour task, inhibitory control in a cylinder test, and persistence and human‑directed behaviour during an unsolvable task. Breeds also differed significantly in their behaviour towards an unfamiliar person, activity level, and exploration of a novel environment. No significant differences were identified in tasks measuring memory or logical reasoning. Breed differences thus emerged mainly in tasks measuring social cognition, problem‑solving, and inhibitory control. Our results suggest that these traits may have come under diversifying artificial selection in different breeds. These results provide a deeper understanding on breed‑specific traits in dogs.